Correlation Between Clinical And Magnetic Resonance Imaging Findings In Patients With Lumbosacral Radiculopathy - Sarkar, Mukul Kumar; Kundu, Pijush Kumar; Alahi, Md Munzur; Amin, Md Pervez; Mallick, Achinta Kumar; Ahmed, Quamruddin; Kafiluddin, Md (TAJ: Journal of Teachers Association, 2018)
Low back pain accounts for a large amount of loss of productivity in the workforce. When the low back pain extends into the lower limb along the distribution of a dermatome then radiculopathy is said to be present. Although most people experience back pain during their lifetime, only a fraction experience lumbosacral radiculopathy as a consequence of nerve root compression or irritation. Almost 5% males and 2.5% females experience lumbosacral radiculopathy at some time in their lifetime. Magnetic resonance imaging (MRI) is the preferred investigation for the diagnosis of lumbosacral radiculopathy. So, in the evaluation of a patient of lumbosacral radiculopathy is essential to correlate clinical symptoms and signs with the finding detected in the MRI to arrive at a correct diagnosis and arrange an appropriate management. So this study was done to see the correlation between clinical and MRI finding of radiculopathy at different nerve root level in patients with lumbosacral radiculopathy. It was a cross sectional descriptive study. All 40 patients of lumbosacral radiculopathy who were presented to Rajshahi Medical College Hospital during the study period from 01/11/2011 to 30/10/2012 were included in the study. There were 30 males and 10 females having an M: F ratio of 3:1. Mean age of total patients 43 + 14.74 years. 67.5% patients were between 20 to 50 years and 60% patients were performing heavy work. 67.5% patients had unilateral involvement while 32.6% patients had bilateral involvement. 72.5% patients had muscle weakness and 27.5% had no muscle weakness. 67.5% patients had sensory impairment and 32.5% had no sensory involvement. Knee jerk changes were present in 60% patients and ankle jerk changes in 66.66% patients. As expected 52.18% had L5 and 32.61% had S1 radiculopathy. The difference in clinical and MRI detection of root involvement was statistically significant (p value < 0.05) in both sides at L4, L5 and S1 root levels but there was no significant difference at the L3 root level (p value 1.00) Intervertebral disc herniation was the commonest cause of lumbosacral radiculopathy (72.32%) and second common cause was spinal canal stenosis (19.44%). Others are intervertebral disc budging (61.52%), disc protrusion (23.08%) and disc extrusion (15.38%). Correlation between clinical severity and MRI grading of lumbosacral radiculopathy which was statistically significant. So, it is concluded that clinical findings correlate well with MRI finding, but all MRI abnormalities need not have a clinical significance TAJ 2015; 28(1): 32-39